(untitled) (Journal of Technology and Operations Management, 2016)
Internal supply chain management can be defined as a set of activities or functions within the firm, which provides products to customers and more attention given to services in manufacturing firms. This process involves a variety of functions in firms such as production, distribution and sales. Internal supply chain management referring as similar to the definition of service in manufacturing. The government aims to promote manufacturing-related services such as product design, research and development (R&D) and central utility supply. This initiative will help to extend the value chain and increase the country’s demand for Malaysian goods and services. Therefore, the supply chain plays an important role in directing and controlling the direction of economic development, this process will make it more efficient and effective. In Malaysia, corporate communication plays significant function in ensuring the efficiency of the service operations which subsequently leads to the excellence performance of the manufacturing. Due to the importance of corporate communication in the manufacturing sector, this paper aims to explore the contribution of corporate communication towards the business development in manufacturing industries.